Analysis of the Potential Use of Mining Waste as Raw Material in the Production of Environmentally Friendly Construction Materials - Rafiuddin Rafiuddin; Bunga Hati (Ali Institute of Research and Publication, 2026)
This study evaluates the feasibility of using three mining-related waste materials, namely tailings, steel slag, and fly ash, as alternative raw materials for environmentally friendly construction products. Although these wastes have been widely examined in previous studies, comparative experimental evidence under a unified testing scheme remains limited, particularly in the Indonesian construction context where material variability and standardization constraints affect field adoption. The novelty of this study lies in positioning the three waste types within the same performance framework by examining compressive strength, water absorption, and corrosion-related durability indicators against a conventional control mixture. Laboratory tests were conducted using a screening-scale experimental design. Compressive strength testing followed the principle of ASTM C39/C39M, water absorption testing followed ASTM C642, and corrosion-related mass/thickness loss evaluation was adapted from laboratory immersion corrosion principles. The results indicate that slag-based specimens showed the highest performance among the waste-based materials, with 28-day compressive strength of 42.1 MPa and water absorption of 3.7%. Fly ash-based specimens reached 36.5 MPa but showed higher water absorption of 6.8%, while tailing-based specimens reached 34.0 MPa with 4.7% water absorption. Compared with the conventional control specimen, the slag-based material achieved approximately 93.6% of the control compressive strength, suggesting its technical potential for selected construction applications after durability and environmental safety validation. The study contributes a comparative performance map and a methodological basis for further optimization of mining waste utilization in sustainable construction materials.